1994
DOI: 10.1289/ehp.94102s5269
|View full text |Cite
|
Sign up to set email alerts
|

Biopersistence of nonfibrous mineral particles in the respiratory tracts of subjects following occupational exposure.

Abstract: Transmission electron microscopy analysis (TEMA) was used to analyze the bronchoalveolar lavage fluid (BALF) of 262 subjects occupationally exposed (OE) to nonfibrous mineral particles (NFMP) and 42 controls not occupationally exposed to mineral dusts. OE subjects were divided into three groups according to the lapse of time since last exposure: <1 year (El), >1 year and <10 years (E2), .10 years (E3). The total BALF mineral particle concentration was significantly higher in OE patients than in controls and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(31 reference statements)
2
2
0
Order By: Relevance
“…Alternatively, our data are also consistent with various forms of aluminium oxides (such as alumina trihydroxide Al(OH) 3 or crystallized alumina Al 2 O 3 , either α or γ form). As the fibre parameters are similar to those reported by GILKS and CHURG [14], we consider that the most probable fibre composition was The concentrations of aluminium nonfibrous particles were also high in these five subjects, largely above mean or median values reported for aluminium-containing NFMP in BAL fluid samples or lung tissue samples of controls in previous series analysed in the same laboratory [18,19]. The mean value of aluminium-containing NFMP in BAL fluid was 5.6×10 3 particles·mL -1 (range 0-1.28×10 4 particles·mL -1 ) in the first series of 42 controls [19].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Alternatively, our data are also consistent with various forms of aluminium oxides (such as alumina trihydroxide Al(OH) 3 or crystallized alumina Al 2 O 3 , either α or γ form). As the fibre parameters are similar to those reported by GILKS and CHURG [14], we consider that the most probable fibre composition was The concentrations of aluminium nonfibrous particles were also high in these five subjects, largely above mean or median values reported for aluminium-containing NFMP in BAL fluid samples or lung tissue samples of controls in previous series analysed in the same laboratory [18,19]. The mean value of aluminium-containing NFMP in BAL fluid was 5.6×10 3 particles·mL -1 (range 0-1.28×10 4 particles·mL -1 ) in the first series of 42 controls [19].…”
Section: Discussionsupporting
confidence: 84%
“…As the fibre parameters are similar to those reported by GILKS and CHURG [14], we consider that the most probable fibre composition was The concentrations of aluminium nonfibrous particles were also high in these five subjects, largely above mean or median values reported for aluminium-containing NFMP in BAL fluid samples or lung tissue samples of controls in previous series analysed in the same laboratory [18,19]. The mean value of aluminium-containing NFMP in BAL fluid was 5.6×10 3 particles·mL -1 (range 0-1.28×10 4 particles·mL -1 ) in the first series of 42 controls [19]. Mean values of aluminium-containing NFMP in BAL fluid and lung tissue were 1×10 4 particles·g -1 dry lung tissue in the second series of 10 patients without any known recent occupational exposure to mineral particles [18].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A few reports have shown the relationship between the mineral components of particles in BALF and occupational exposure to mineral dusts. Parion et al showed significantly increased levels of iron in the BALF of 205 occupationally-exposed patients in comparison to 41 patients without occupational exposure, and Bernstein et al also showed that iron was significantly increased in the BALF of 46 dental technicians with lung diseases in comparison to 41 white-collar workers with lung diseases [ 22 , 23 ]. Our results showing an increase of elemental iron detected by EM in BALF in the exposure-positive group are consistent with these previous studies, and the detection of iron may be useful in screening for occupation-related lung diseases.…”
Section: Discussionmentioning
confidence: 99%